2023
DOI: 10.3390/app13074522
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of the Impact of Surface Tension and Viscosity on the Atomization Effect of a Solid Cone Nozzle

Abstract: To investigate the influence of surface tension and viscosity on the atomization performance of solid cone nozzles and improve their dust reduction efficiency in industrial and mining enterprises, this study employed a self-built PDPA dust-fog coupling experimental system to explore the effects of different surface tension and viscosity solutions on atomization performance from three aspects: axial, radial, and fog field distribution. The experimental results indicate that compared with surface tension, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Moreover, closer proximity to the nozzle results in smaller droplet sizes, known for their effectiveness in absorption. Studies have shown a consistent and continuous growth trend in measured droplet sizes within the range of 3 to 13 cm from the nozzle, with the rate of growth exceeding 100% . Elevated gas flow rates at the inlet can also impact droplet behavior, causing oscillation at high gas velocities and subsequently increasing the mass transfer rate compared to nonoscillating droplets.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, closer proximity to the nozzle results in smaller droplet sizes, known for their effectiveness in absorption. Studies have shown a consistent and continuous growth trend in measured droplet sizes within the range of 3 to 13 cm from the nozzle, with the rate of growth exceeding 100% . Elevated gas flow rates at the inlet can also impact droplet behavior, causing oscillation at high gas velocities and subsequently increasing the mass transfer rate compared to nonoscillating droplets.…”
Section: Resultsmentioning
confidence: 91%
“…Studies have shown a consistent and continuous growth trend in measured droplet sizes within the range of 3 to 13 cm from the nozzle, with the rate of growth exceeding 100%. 40 Elevated gas flow rates at the inlet can also impact droplet behavior, causing oscillation at high gas velocities and subsequently increasing the mass transfer rate compared to nonoscillating droplets. The closer gas inlet proximity to the nozzle in a cocurrent spray tower, as opposed to a counter-current spray tower, results in a higher gas flow rate near the nozzle.…”
Section: Comparative Analysis Of Cocurrent Andmentioning
confidence: 99%